A Randomised Controlled Trial of Guided Self-Help Cognitive Behaviour Therapy for Clinical Perfectionism - Hoiles, Kimberley Jo (Curtin University, 2016)
Perfectionism has been found to be elevated across disorders, with evidence that it can interfere with treatment outcome. Study 1, provides evidence of convergent validity of the CPQ in a mixed clinical sample (N = 32). In Study 2, guided self-help CBT for clinical perfectionism decreased perfectionism and psychopathology in an elevated perfectionism sample (N = 40) with self-criticism mediating treatment outcome. The intervention also reduced primary DSM-IV diagnosis and comorbid presentations.